2022
DOI: 10.3390/ijerph19031867
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pharmacists’ Willingness to Conduct Medication Use Reviews in Poland

Abstract: Introduction. Pharmacists play an important role in healthcare. Their functions are evolving and, in many countries, they actively participate in interdisciplinary patient treatment. One of the most common services provided by pharmacists as part of pharmaceutical care in community pharmacies involves medication reviews. Objective. The objective of this study was to evaluate the readiness of pharmacists to conduct medication reviews in community pharmacies. Materials and methods. This study comprises 493 pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…This is in line with Kirklade et al's study [35], where the flu vaccination service in community pharmacies was beneficial and is seen as an integral part of the healthcare system in countries like the United States, Canada, England, or Portugal [35]. Moreover, the participation of pharmacists in patient treatment with simultaneous pharmaceutical care improves patient health outcomes [33]. It may contribute to both health and economic benefits in healthcare.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This is in line with Kirklade et al's study [35], where the flu vaccination service in community pharmacies was beneficial and is seen as an integral part of the healthcare system in countries like the United States, Canada, England, or Portugal [35]. Moreover, the participation of pharmacists in patient treatment with simultaneous pharmaceutical care improves patient health outcomes [33]. It may contribute to both health and economic benefits in healthcare.…”
Section: Discussionsupporting
confidence: 74%
“…As in our study, Merks et al [33] revealed that pharmacists in Poland are willing to broaden the scope of services offered in community pharmacies [32,36]. However, most pharmacists in the study agreed that the public healthcare payer or private insurer and the patient should partially fund such services.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Despite the development of pharmaceutical care worldwide, the level of care in Poland in this regard is much lower. However, a study by Merks et al found that pharmacists in Poland expressed a willingness to conduct medical reviews, which could have a significant impact on optimizing patient health outcomes [35]. Many studies confirm the influence of pharmacists on the safety of patients' therapies by providing information on medication use.…”
Section: Discussionmentioning
confidence: 99%
“…Due to an aging population, polypharmacy and inappropriate prescribing are expected to rise in the Eastern European region. While there are barriers at the healthcare policy and organizational levels, community pharmacists are well placed and willing to offer MRs to promote the rational use of medicines and benefit patients (Tuula et al, 2021;Merks et al, 2022;Paidere et al, 2023).…”
Section: Introductionmentioning
confidence: 99%